2009
DOI: 10.3342/ceo.2009.2.4.181
|View full text |Cite
|
Sign up to set email alerts
|

Initial Adherence to Autotitrating Positive Airway Pressure Therapy: Influence of Upper Airway Narrowing

Abstract: ObjectivesThere is still debate concerning the reason for the high initial failure rate of positive airway pressure (PAP) treatment. The objective of this study is to investigate the factors of the initial adherence to PAP, with an emphasis on the role of upper airway narrowing.MethodsThe patients were divided into two groups according to the continuation of therapy within the first three months of treatment. The demographic and polysomnographic findings, the minimal nasal cross sectional area (MCA), the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Second, nasal obstruction was measured from self‐reported symptoms, which may not correlate well with actual resistance to nasal airflow. Nasal resistance based on rhinomanometry and acoustic rhinometry has been found to be associated with poorer nasal CPAP adherence in some studies, but not in others . More studies will be needed to evaluate if functional and anatomical measurements of nasal obstruction may be associated with differences in adherence to mask interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Second, nasal obstruction was measured from self‐reported symptoms, which may not correlate well with actual resistance to nasal airflow. Nasal resistance based on rhinomanometry and acoustic rhinometry has been found to be associated with poorer nasal CPAP adherence in some studies, but not in others . More studies will be needed to evaluate if functional and anatomical measurements of nasal obstruction may be associated with differences in adherence to mask interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate the need of good nasal patency during the patient's initial adaptation to the device. So et al [ 63 ] also investigated 36 patients using acoustic rhinometry and observed that the sum of the nasal area was greater in the group of patients with good CPAP adherence, but only in those with AHI < 60/hour.…”
Section: Nasal Obstruction and Cpapmentioning
confidence: 99%
“…2 For successful CPAP therapy, an effort to enhance or improve compliance is very important. 8,9 In our previous study with Korean patients with OSAS, a predictive equation for an optimal CPAP level was developed using body mass index (BMI) and AHI, which can be easily measured during the diagnostic process. 10 It is well recognized that fullnight manual titration in a sleep laboratory is the preferred method.…”
Section: Introductionmentioning
confidence: 99%